Implementation of website for Hind Enterprises Product: A Literature Review on Electronics perspectives, trends, and future directions - Savata Bankar; Sarthak Lagad; Makarand Jadhav; P.M. Sawant; A.S. Deokate (International Journal of Solid State Innovations & Research, 2024)
The aim of Hind Enterprises’ product website is to develop a user friendly and informative online platform. That shows a diverse range of products. This website will serve as a comprehensive resource for manufacturing, business and individuals seeking information about machinery offering, specification and uses. The website will feature an intuitive and visually appealing design, ensuring seamless navigation for users. One primary goal of the project is to create a responsive and mobile-friendly website that can be accessed from various devices. Hind Enterprise is a product-based company that offers a variety of tools, including machinery. We have to define purpose, content and layout of website using text editor, HTML structure, and CSS styling. We have to create websites using writing HTML code for website structure including headings, paragraphs, lists and other elements. We have to create CSS files to style the website like define rules for front, colors, spacing, and layout; optimization of image and for loading times. The success of this project will be measured through user feedback, performance metrician and achievement of the predefined goal. The implementation of Hind Enterprises website is to provide potential benefits and impact to user experiences, increase engagement, and improve online presence.
Keywords: 3D models; User experience; Web design; frontend; user interface; world wide web